Pengaruh Fleksibilitas Kerja dan Keterampilan Terhadap Kinerja Karyawan di Perusahaan Kuningan Desa Karangrejo Juwana - Ana Febriyanti; Suparmi Suparmi; Sulistiyani Sulistiyani; Camilus Isidorus Ikut (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
The purpose of this study is to examine how a brass manufacturing company in Karangrejo Village, Juwana, addresses the impact of skills and work flexibility on employee performance. Improving employee performance is crucial, and previous research has shown conflicting findings when examining the impact of these two factors. This is the rationale for this study. Using census methodology as the sampling method, the study population consisted of seventy-six individuals from six different brass manufacturing companies. To analyze the data, multiple linear regression was used on the administered questionnaire. The results indicate that employee performance is positively and significantly influenced by work flexibility. Workplace performance is positively and significantly influenced by worker ability. Accountability, punctuality, quantity, and quality of employee work significantly improve with increased work flexibility and skills. These findings suggest that the implementation of controlled work flexibility and continuous skills development can optimally improve employee performance. This study implies that companies need to design adaptive work policies and appropriate training programs to support the achievement of production targets and organizational sustainability.